Subtle shifts in fecal microbiota diversity during early stages of Mycobacterium avium subsp. paratuberculosis pathogenesis in dairy cattle - P. Steuer; C. Tejeda; J.M. Hernández-Agudelo; F. Ulloa; M.F. Addis; M. Salgado (Veterinary Microbiology, 2026)

Dispersal Propensity and Dispersal Distance Are Genetically Independent Traits in a Stream Salamander - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane (Molecular Ecology, 2026)
Empirical understanding of dispersal evolution is limited, due in large part to the complexity of the dispersal process and the difficulty of quantifying dispersal directly. To move ahead, it may help to focus on universal dispersal traits: propensity—the discrete emigration response distinguishing dispersers from non‐dispersers—and distance. In particular, little is known about the evolution of dispersal distance, including whether it is an independent trait subject to selection. We used capture‐recapture data and single nucleotide polymorphism (SNP) genotypes from 1906 salamanders sampled over 10 years to test for independent genetic associations with dispersal propensity and distance. Gyrinophilus porphyriticus is a headwater specialist, and our data are from three hydrologically independent streams in New Hampshire. We quantified dispersal propensities and distances directly with recapture histories and we used principal component analysis of SNP genotypes to derive three orthogonal axes of genetic variation. Of 173 recaptured individuals, 81 were non‐dispersers and 92 were dispersers based on an empirically derived 3‐m threshold distinguishing dispersal from movements within an individual's home range. Dispersal distances ranged from 4 to 1248 m. Dispersal propensity and distance were significantly associated with different axes of genetic variation, indicating that these are independent traits capable of responding to different selective forces. More broadly, these results show that quantifying dispersal propensities and dispersal distances—and explicitly assessing interactions and trade‐offs between these traits—may help to advance understanding of dispersal evolution.

Advanced characterization of fouling in reverse osmosis membrane: Implications for Brackish groundwater treatment - Ilham Karmal; Jamila El Gaayda; Sara Darbal; Mustapha Nassiri; Mohamed El Housse; M’barek Belattar; Said Ben-Aazza; Naima Hafid; Abdelaziz Ait Addi; Rachid Ait Akbour; Ali Driouiche (Groundwater for Sustainable Development, 2026)

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Magnetically recoverable PANI@α-Fe2O3-montmorillonite for fast simultaneous removal of Cr(VI) and OG dye from synthetic and actual wastewater - Fatima-Zahra Mahir; Hamid Zouggari; Aida M. Díez; Ridha Djellabi; Marta Pazos; Lahcen Bazzi; Mohamed Laabd; Abdallah Albourine; Abdelaziz Ait Addi (Environmental Research, 2025)

Efficient photocatalytic removal of ciprofloxacin antibiotic by dual Z-scheme Ag3PO4/g-C3N4/Bi2WO6 under solar irradiation - M. Rhaya; H. Abou Oualid; R.E. Malekshah; B. Ennasraoui; H. Ighnih; H. Ouachtak; A. Jada; A. Ait Addi (Journal of Water Process Engineering, 2025)

Rare earth elements and yttrium in Polish rivers and the input of anthropogenic gadolinium into the Baltic Sea - Addis Kokeb Alemu; Keran Zhang; David M. Ernst; Michael Bau (Environmental Pollution, 2025)

Pedogenic variables with color indices of rubified Alfisols in the Kakalachinte microwatershed, Karnataka, South India - Gizachew Ayalew Tiruneh; Ashok Hanjagi; Bhaskara Phaneendra; M. Lalitha; R. Vasundhara; V. Ramamurty; S. Abdul Rahaman; T. Ravikiran; Agmas Amare Simegn; Tewodros Mulu Addis; Derege Tsegaye Meshesha; Tiringo Yilak Alemayehu; et al. (Geoderma Regional, 2024)

Population structure and genetic diversity of Moroccan cannabis (Cannabis sativa L.) germplasm through simple sequence repeat (SSR) analysis - Chaymae Benkirane; Majida Charif; Christina M. Müller; Yassine Taaifi; Farid Mansouri; Mohamed Addi; Mohammed Bellaoui; Hana Serghini-Caid; Ahmed Elamrani; Malika Abid (Genetic Resources and Crop Evolution, 2024)

Outbreeding reduces survival during metamorphosis in a headwater stream salamander - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane (Molecular Ecology, 2024)
Assessing direct fitness effects of individual genetic diversity is challenging due to the intensive and long‐term data needed to quantify survival and reproduction in the wild. But resolving these effects is necessary to determine how inbreeding and outbreeding influence eco‐evolutionary processes. We used 8 years of capture–recapture data and single nucleotide polymorphism genotypes for 1906 individuals to test for effects of individual heterozygosity on stage‐specific survival probabilities in the salamander Gyrinophilus porphyriticus . The life cycle of G. porphyriticus includes an aquatic larval stage followed by metamorphosis into a semi‐aquatic adult stage. In our study populations, the larval stage lasts 6–10 years, metamorphosis takes several months, and lifespan can reach 20 years. Previous studies showed that metamorphosis is a sensitive life stage, leading us to predict that fitness effects of individual heterozygosity would occur during metamorphosis. Consistent with this prediction, monthly probability of survival during metamorphosis declined with multi‐locus heterozygosity (MLH), from 0.38 at the lowest MLH (0.10) to 0.06 at the highest MLH (0.38), a reduction of 84%. Body condition of larvae also declined significantly with increasing MLH. These relationships were consistent in the three study streams. With evidence of localised inbreeding within streams, these results suggest that outbreeding disrupts adaptations in pre‐metamorphic and metamorphic individuals to environmental gradients along streams, adding to evidence that headwater streams are hotspots of microgeographic adaptation. Our results also underscore the importance of incorporating life history in analyses of the fitness effects of individual genetic diversity and suggest that metamorphosis and similar discrete life stage transitions may be critical periods of viability selection.

Electro-Fenton process for treatment of hydroxybenzoic acids solutions using boron-doped diamond/carbon-felt cells: application to olive mill wastewater - A. Sennaoui; F. Sakr; S. Alahiane; M. Dinne; A. Assabbane; E. Ait Addi (International Journal of Environmental Science and Technology, 2024)

Individual growth rates and size at metamorphosis increase with watershed area in a stream salamander - Madaline M. Cochrane; Brett R. Addis; Leah K. Swartz; Winsor H. Lowe (Ecology, 2024)
A fundamental goal of ecology is to understand how the physical environment influences intraspecific variability in life history and, consequently, fitness. In streams, discharge and associated habitat conditions change along a continuum from intermittency to permanence: Headwater streams typically have smaller watersheds and are thus more prone to drying than higher‐order streams with larger watersheds and more consistent discharge. However, few empirical studies have assessed life history and associated population responses to this continuum in aquatic organisms. We tested the prediction that individual growth, rate of development, and population growth increase with watershed area in the long‐lived stream salamander Gyrinophilus porphyriticus , where we use watershed area as a proxy for hydrologic intermittence. To address this hypothesis, we used 8 years of mark–recapture data from 53 reaches across 10 headwater streams in New Hampshire, USA. Individual growth rates and mean size at metamorphosis increased with watershed area for watersheds from 0.12 to 1.66 km 2 . Population growth rates increased with watershed area; however, this result was not statistically significant at our sample size. Mean age of metamorphosis did not vary across watershed areas. Lower individual growth rates and smaller sizes at metamorphosis likely contributed to reduced lifetime fecundity and population growth in reaches with the smallest watershed areas and highest vulnerability to drought. These responses suggest that as droughts increase due to climate change, headwater specialists in hydrologically intermittent environments will experience a reduction in fitness due to smaller body sizes or other growth‐related mechanisms.

Unidirectional trans‐Atlantic gene flow and a mixed spawning area shape the genetic connectivity of Atlantic bluefin tuna - Natalia Díaz‐Arce; Pierre‐Alexandre Gagnaire; David E. Richardson; John F. Walter; Sophie Arnaud‐Haond; Jean‐Marc Fromentin; Deirdre Brophy; Molly Lutcavage; Piero Addis; Francisco Alemany; Robert Allman; Simeon Deguara; et al. (Molecular Ecology, 2024)
The commercially important Atlantic bluefin tuna ( Thunnus thynnus ), a large migratory fish, has experienced notable recovery aided by accurate resource assessment and effective fisheries management efforts. Traditionally, this species has been perceived as consisting of eastern and western populations, spawning respectively in the Mediterranean Sea and the Gulf of Mexico, with mixing occurring throughout the Atlantic. However, recent studies have challenged this assumption by revealing weak genetic differentiation and identifying a previously unknown spawning ground in the Slope Sea used by Atlantic bluefin tuna of uncertain origin. To further understand the current and past population structure and connectivity of Atlantic bluefin tuna, we have assembled a unique dataset including thousands of genome‐wide single‐nucleotide polymorphisms (SNPs) from 500 larvae, young of the year and spawning adult samples covering the three spawning grounds and including individuals of other Thunnus species. Our analyses support two weakly differentiated but demographically connected ancestral populations that interbreed in the Slope Sea. Moreover, we also identified signatures of introgression from albacore ( Thunnus alalunga ) into the Atlantic bluefin tuna genome, exhibiting varied frequencies across spawning areas, indicating strong gene flow from the Mediterranean Sea towards the Slope Sea. We hypothesize that the observed genetic differentiation may be attributed to increased gene flow caused by a recent intensification of westward migration by the eastern population, which could have implications for the genetic diversity and conservation of western populations. Future conservation efforts should consider these findings to address potential genetic homogenization in the species.

LP-36: The Clariant CompTox Suite – Towards implementation of predictive toxicology approaches to support discovery of chemical alternatives that are safe and sustainable by design - Q. Li; K. Addis; D. Becker; L. Bodelon; K. Framesqui; M. Hufnagel; A. Marson; F.A. Grimm (Toxicology Letters, 2023)

Source–sink dynamics within a complex life history - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane; Leah K. Swartz (Ecology, 2023)
Source–sink patch dynamics occur when movement from sources stabilizes sinks by compensating for low local vital rates. The mechanisms underlying source–sink dynamics may be complicated in species that undergo transitions between discrete life stages, particularly when stages have overlapping habitat requirements and similar movement abilities. In these species, for example, the demographic effects of movement by one stage may augment or offset the effects of movement by another stage. We used a stream salamander system to investigate patch dynamics within this form of complex life history. Specifically, we tested the hypothesis that the salamander Gyrinophilus porphyriticus experiences source–sink dynamics in riffles and pools, the dominant geomorphic patch types in headwater streams. We estimated stage‐specific survival probabilities in riffles and pools and stage‐specific movement probabilities between the two patch types using 8 years of capture–recapture data on 4491 individuals, including premetamorphic larvae and postmetamorphic adults. We then incorporated survival and movement probabilities into a stage‐structured, two‐patch model to determine the demographic interactions between riffles and pools. Monthly survival probabilities of both stages were higher in pools than in riffles. Larvae were more likely to move from riffles to pools, but adults were more likely to move from pools to riffles, despite experiencing much lower survival in riffles. In simulations, eliminating interpatch movements by both stages indicated that riffles are sinks that rely on immigration from pools for stability. Allowing only larvae to move stabilized both patch types, but allowing only adults to move destabilized pools due to the demographic cost of adult emigration. These results indicated that larval movement not only stabilizes riffles, but also offsets the destabilizing effects of maladaptive adult movement. Similar patch dynamics may emerge in any structured population in which movement and local vital rates differ by age, size, or stage. Addressing these forms of internal demographic structure in patch dynamics analyses will help to refine and advance general understanding of spatial ecology.

The H2O content of the ureilite parent body - Liam D. Peterson; Megan E. Newcombe; Conel M. O'D. Alexander; Jianhua Wang; Adam R. Sarafian; Addi Bischoff; Sune G. Nielsen (Geochimica et Cosmochimica Acta, 2023)

Alterations of endophytic microbial community function in Spartina alterniflora as a result of crude oil exposure - Samantha D. Addis; Stephen K. Formel; Yeon Ji Kim; Paige B. Varner; Daniel B. Raudabaugh; Emilie Lefevre; Brittany M. Bernik; Vijaikrishnah Elango; Sunshine A. Van Bael; John H. Pardue; Claudia K. Gunsch (Biodegradation, 2022)

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

In silico determination of nitrogen metabolism in microbes from extreme conditions using metagenomics - Lulit Tilahun; Asfawossen Asrat; Gary M. Wessel; Addis Simachew (Archives of Microbiology, 2021)

The effects of muscle blood flow restriction during running training on measures of aerobic capacity and run time to exhaustion - Carl D. Paton; Shalako M. Addis; Lee-Anne Taylor (European Journal of Applied Physiology, 2017)

DISTRIBUTION OF SPAWNING AND NURSERY GROUNDS FOR DEEP–WATER RED SHRIMPS IN THE CENTRAL WESTERN MEDITERRANEAN SEA - F. PALMAS; P. ADDIS; S. CABIDDU; D. CUCCU; M. C. FOLLESA; M. MURA; A. OLITA; P. PESCI; A. SABATINI (Mediterranean Marine Science, 2014)
The presence of spawning and nursery grounds of Aristeids in the central western Mediterranean Sea were investigated using fishery-independent data (trawl surveys, 1994–2012). Spatial distributions were generated for mature animals and recruits, for both spring/summer and autumn data, using an inverse distance weighted deterministic interpolation. The persistence index was used to identify stable spawning and nursery grounds in the Sardinian slope region for Aristaeomorpha foliacea and Aristeus antennatus. Areas of aggregation for recruits and mature females appear connected with important physical habitat features. The analysis also suggests a seasonal bathymetric distribution for nursery areas. The recruits of A. foliacea are located in the upper part of the continental slope (377-450 m) in spring-summer and reach greater depths (468-628 m) in autumn. For A. antennatus, for which nursery areas only emerge in autumn, there is presumably an opposite ontogenic migration, from deep sea to upper slope, during the summer (575-681 m). Results indicate also a partial overlap between the nursery and spawning grounds of both species. In this particular areas, local environmental conditions such as upwelling events or the presence of canyons and seamounts seem to play an important role in their distribution. This study generated also relevant information on the spatial and temporal distribution of seasonal or persistent aggregations of spawners and recruits, providing scientific elements to suggest the feasibility of protecting these important resources.

Mitochondrial DNA variability of the pipefish Syngnathus abaster - D. Sanna; F. Biagi; H. B. Alaya; F. Maltagliati; A. Addis; A. Romero; J. De Juan; J.‐P. Quignard; A. Castelli; P. Franzoi; P. Torricelli; M. Casu; et al. (Journal of Fish Biology, 2013)
This study provides data on the genetic structuring of the pipefish Syngnathus abaster in the western Mediterranean and Adriatic Seas. A total of 109 specimens were collected in brackish‐water biotopes. The control region and three other regions of the mitochondrial genome were analysed. The most relevant result was the high genetic structuring found by Bayesian inference ( BI ), maximum likelihood ( ML ) and network analyses, which were consistent in showing three well‐separated clusters of S. abaster populations. Furthermore, BI and ML did not support the monophyly of the taxon S. abaster . These results suggest the occurrence of a species complex in the study area, whose differentiation may have occurred since the Pleistocene. The results also show a very high genetic variability at the inter‐population level, with no shared haplotypes among sites. Evolutionary forces due to the fragmented nature of the brackish‐water habitats may account for the high genetic divergence found among the groups and populations. Finally, although dispersal by rafting over long distances may occasionally occur, this study suggests linear stepping‐stone model of colonization to be most likely. The complexity of the results obtained suggests that further studies are needed to elucidate the phylogeny of S. abaster .

Differential accumulation of monolignol-derived compounds in elicited flax (Linum usitatissimum) cell suspension cultures - C. Hano; M. Addi; L. Bensaddek; D. Crônier; S. Baltora-Rosset; J. Doussot; S. Maury; F. Mesnard; B. Chabbert; S. Hawkins; E. Lainé; F. Lamblin (Planta, 2006)